The effects of trauma-focused research on pregnant female participants. - Goff, Briana S. Nelson; Schwerdtfeger, K.L. (My University, 2008)
Recent emphasis on the ethical conduct of researchers has resulted in a growing body of literature exploring the impact of trauma-focused research on participants. To date, pregnant women have not been widely included in trauma-focused research, possibly because they are considered a vulnerable population in research. The current research investigated how 41 expectant mothers responded to participation in a trauma-focused study. Overall, the results of this study suggest that trauma-focused research is well tolerated by pregnant women. Specific findings indicated that pregnant women considered more traumatized perceived greater benefits from participation. Best practices for conducting ethical trauma-focused research with pregnant women are provided. As well, recommendations for future research are outlined in an effort to further extend the ethical understanding of the benefits and costs of trauma-focused research with potentially vulnerable populations.
Keywords: Trauma-focused research; Research subjects; Pregnancy; Women; Ethics; Risk-benefit analysis